Development of Canva-Based Digital Scrapbook Learning Media Using The ADDIE Model in Indonesian Language Learning Material Writing Short Story Text - Kinasih Dwijayanti; Ibut Priono Leksono; Ujang Rohman (Indonesia Approach Education, 2022)
Writing skills in Indonesian language learning include many texts. One of them is short story text. However, sometimes, learning to write short stories becomes boring. This happens if the teacher does not provide innovation and the right strategy in the learning process so that it runs effectively in accordance with the learning objectives. The development of science and technology requires teachers to be able to develop skills in making learning media. This research uses the Research and Development method and the model used is ADDIE. This research method is used to produce certain products and test the effectiveness of these products. Based on the assessment of design experts, a score of 85.71% was obtained, an assessment by media experts obtained a percentage score of 85.71%, and a material expert assessment with a percentage score of 90%. Based on the results of validation conducted by design experts and media experts, the results obtained are included in the